2014
DOI: 10.3892/mmr.2014.2079
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy may protect MC3T3-E1 cells from fluoride-induced apoptosis

Abstract: Abstract.Fluoride is an essential trace element for all mammalian species; however, excess fluoride intake is known to be toxic to cells in animals and humans. The toxicity of fluoride is mainly exerted via induction of apoptosis. Autophagy is induced by numerous cytotoxic stimuli; however, it is often unclear whether, under specific conditions, autophagy has a pro-survival or a pro-apoptotic role. To answer this critical question, the present study assessed autophagy and apoptosis simultaneously in single cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
(24 reference statements)
3
12
0
Order By: Relevance
“…This result is consistent with current related studies in osteoblasts 38, 39. Many factors can affect both the autophagy and apoptosis of osteoblasts, including fluoride, high glucose, and paxilitaxel 40-42. However, the effect of DMT1 on the apoptosis and autophagy of osteoblasts is first reported here.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with current related studies in osteoblasts 38, 39. Many factors can affect both the autophagy and apoptosis of osteoblasts, including fluoride, high glucose, and paxilitaxel 40-42. However, the effect of DMT1 on the apoptosis and autophagy of osteoblasts is first reported here.…”
Section: Discussionsupporting
confidence: 93%
“…Previous investigations have shown that fluoride induces autophagy in the LS8 ameloblast cell line and in MC3T3-E1 osteoblastic cells [Suzuki and Bartlett, 2014;Wei et al, 2014]. However, few studies have investigated whether fluoride induces autophagy in the rat ameloblast cell line HAT-7.…”
Section: Discussionmentioning
confidence: 99%
“…The functional relationship between autophagy and apoptosis is complex under certain circumstances. Autophagy may play a protective role in fluoride-induced apoptosis [Wei et al, 2014]. However, Mizushima et al [2008] found that excessive autophagy damaged a large number of proteins and intracellular organelles, finally causing cell death.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been postulated that the regulation of p62 is responsible for controlling the formation of intracellular inclusion bodies in autophagy, and Beclin1 is involved in the initial steps of the formation of autophagosomes. Recently, it was demonstrated that uoride also induces autophagy due to an increased expression of Beclin1 and LC3 and a decreased expression of p62 in osteoblasts [17,45]. Similarly, a dose-response pattern in LC3-II protein expression in ameloblastderived cells has been observed with uoride treatment [30], which decreases after increasing the concentration of uoride.…”
Section: Discussionmentioning
confidence: 92%
“…Autophagy is a quintessential component of a multitude of cellular and tissue metabolic events [16] and it has also been considered as a key component of tissue protective mechanisms against the detrimental effects of extrinsic factors [17]. Autophagy-related 5 (ATG5), Beclin1, LC3 and p62 play pivotal roles in the autophagy pathway.…”
Section: Introductionmentioning
confidence: 99%